Strong solutions to the inhomogeneous Navier–Stokes–BGK system. (February 2021) - Choi, Young-Pil; Lee, Jaeseung; Yun, Seok-Bae
Abstract: In this paper, we are concerned with the local-in-time well-posedness of a fluid-kinetic model in which the BGK model with density dependent collision frequency is coupled with the inhomogeneous Navier–Stokes equation through drag forces. To the best knowledge of authors, this is the first result on the existence of local-in-time smooth solution for particle–fluid model with nonlinear inter-particle operator for which the existence of time can be prolonged as the size of initial data gets smaller.